Intentions to drop-out of youth soccer: A test of the basic needs theory among European youth from five countries - Quested, E.; Ntoumanis, Nikos; Viladrich, C.; Haug, E.; Ommundsen, Y.; Van Hoye, A.; Mercé, J.; Hall, H.; Zourbanos, N.; Duda, J. (Taylor & Francis Inc., 2012)
Research arising from self-determination theory (SDT; Deci, E. L., & Ryan, R. M. (2000). The “what” and “why” of goal pursuits: Human needs and the self-determination of behavior. Psychological Inquiry, 11(4), 227–268) indicates that the quality of the social interactions between athletes and coaches, and athletes' ensuing psychological responses, are critical determinants of intentions to drop out of youth sport. Little is known regarding whether these processes hold across countries. Grounded in SDT, this study tested the invariance of a model predicting youth sport dropout across five European countries. Seven thousand seven hundred and sixty-nine grassroots players (6641 males, 1020 females (M age = 11.56, SD = 1.40) from youth soccer teams in five countries (England, France, Greece, Norway, and Spain) completed a questionnaire tapping perceptions of coach-provided autonomy support, basic psychological need satisfaction (i.e. autonomy, competence and relatedness), soccer enjoyment, and intentions to drop out of soccer in the next season. Data were analysed using structural equation modelling. The hypothesised model (autonomy support → basic needs → enjoyment → intentions to drop out of soccer) showed an acceptable fit to the data and provided evidence of configural factor loading and structural path invariance across the five countries. This study supports the applicability of the basic needs theory model as a framework to understand the determinants of drop out intentions in sport among European youth across national boundaries. Findings highlight a potential avenue for intervention that could impact children's enjoyment of, and intentions to continue, playing soccer; namely, interventions that specifically target autonomy supportive coaching.